A hydra de 25 cabeças: jogo do bicho, imprensa e vida urbana em São Paulo (1890-1920) - Lemo, Felipe Arroyo (2024)
The current research project proposes an analysis of the phenomenon of the “jogo do bicho” (animal game) in São Paulo during the late 19th and early 20th centuries. The scope of the investigation extends beyond the mere identification of gambling practices, delving into the intricate codes of conduct prevalent in this specific historical context. Furthermore, the study aims to highlight the dynamics of urban spaces where the “jogo do bicho” manifested, unraveling the complex interactions between individuals and the city. An additional focus is placed on moralizing campaigns waged against this practice, seeking to understand the conflict between prevailing social norms and cultural expressions that challenged such standards. By addressing these elements in an integrated manner, the goal is to provide a more comprehensive and in-depth understanding of the role of the “jogo do bicho” in the social and cultural fabric of late 19th-century and early 20th-century São Paulo